Derivatives of the triglyceride–glucose index and their association with incident hypertension in prehypertensive individuals: a 4-year cohort study augmented by mendelian randomization - Mengmeng Wang; Tianqi Teng; Nan Zhang; Jiachao Xu; Zihan Dong; Qingying Jiao; Ning Zhang; Haichu Yu (Cardiovascular Diabetology)
Abstract Background The direct association between elevated levels of the triglyceride-glucose index (TyG index) and its derived metrics and the risk of new-onset hypertension in prehypertensive populations remains unclear. The study systematically evaluated the link between the TyG index and its related indicators with new-onset hypertension by integrating cohort study methods with Mendelian randomization (MR) analysis. Methods A total of 2,815 prehypertensive participants from the 2011 CHARLS database were included, of whom 877 (31.15%) progressed to new-onset hypertension by 2015. TyG-Waist-to-Height Ratio (TyG-WHtR), TyG-Body Mass Index (TyG-BMI), TyG-Waist Circumference (TyG-WC), and the TyG index were calculated. Logistic regression, restricted cubic spline (RCS) curves, subgroup analyses, and interaction tests were performed to assess the associations. Bayesian weighted MR (BWMR) was further used to validate causal relationships. Results Multivariable regression analysis revealed that each unit increase in the TyG index was associated with a 45% higher risk of new-onset hypertension (odds ratio [OR]: 1.45, 95% confidence intervals [CI] 1.24–1.70, P < 0.001), while TyG-WHtR showed a 42% increased risk (OR: 1.42, 95% CI 1.26–1.60, P < 0.001). Categorizing the TyG and its derived metrics by quartiles demonstrated that higher quartiles (Q3 and Q4) were significantly linked to an elevated risk of new-onset hypertension across all models (P < 0.001). RCS models indicated significant positive linear relationships between the TyG index and TyG-WC with new-onset hypertension (P for overall < 0.001, P for nonlinearity = 0.844 and 0.165, respectively), whereas TyG-WHtR and TyG-BMI exhibited significant positive nonlinear relationships (P for overall < 0.001, P for nonlinearity = 0.001 and 0.046, respectively). Subgroup analyses highlighted stronger associations among individuals aged ≥ 70 years, those who were widowed, had cardiovascular disease, or reported a life satisfaction score of 2 (P < 0.05, P for interaction < 0.05). BWMR analysis confirmed a significant causal relationship between genetically elevated TyG index levels and an increased risk of new-onset hypertension (P < 0.05). Conclusions Our study reveals a significant link between the TyG index and its related indicators with new-onset hypertension in prehypertensive populations. Causal analysis using BWMR confirmed that genetically elevated TyG index levels increase the risk of new-onset hypertension. These results highlight the importance of monitoring TyG-related indices for early detection and intervention in high-risk individuals, aiding in the prevention of hypertension progression. Graphical abstract